Hong Kong SAR Economic Integration with the Pearl River Delta - Unteroberdoerster, Olaf.; Chen, Hongyi (Washington, D.C. : International Monetary Fund, 2008)
Hong Kong SAR's economic integration with the Mainland has primarily taken place in the Pearl River Delta (PRD). Taking stock of integration trends, this paper discusses key implications for ensuring economic benefits of further integration are sustained and associated costs minimized. Besides further investments in infrastructure, Hong Kong SAR's role as a producers services and finance hub will depend on frictionless movements of goods, services, people and know-how, requiring policy coordination to further promote trade and investment and developing a common human skills base with the PRD. Regional cooperation will also be needed to minimize the costs of rising levels of cross-border pollution.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet